Альтернативные жидкие топлива: достижения и перспективы; Успехи химии; Т. 94, № 5 - Стрижак П. А. Павел Александрович; Алдошин С. М.; Глушков Д. О. Дмитрий Олегович; Дементьев К. И. Константин Игоревич; Ивашкина Е. Н. Елена Николаевна; Куликова М. В. Майя Валерьевна; Максимов А. Л. Антон Львович; Назарова Г. Ю. Галина Юрьевна; Носков А. С. Александр Степанович; Пармон В. Н. Валентин Николаевич; Паушкина К. К. Кристина Константиновна; Попок Е. В. Евгений Владимирович; et al. (2025, 2025)
Заглавие с экрана